Toward Sustainable Tourism: Insights for Mactor Analysis In Ngebel Lake, Indonesia - Mugi Rahardjo; Evi Gravitiani; Ika Alicia Sasanti (Economics Development Analysis Journal, 2023)
Sustainable tourism development requires the synergy of actors' and actors' attitudes in responding to goals and opportunities for conflict to arise due to resistance between actors and goals. This study aims to identify stakeholder actors, identify the strengths and attitudes of actors towards sustainable tourism development goals and describe the pattern of linkage between actors with development goals in Ngebel Lake. This research uses a sequential mixed method that combines quantitative and qualitative approaches sequentially in all stages of the research process. Data collection methods using in-depth interviews with actors. Data analysis using MACTOR software to identify stakeholder actors' strengths, relationships, and alliance patterns. The results showed that Local Communities, Small and Medium enterprises, and the Services Office of Environment are the dominant actors in tourism development in the Ngebel Lake area. Meanwhile, The Department of Youth Sports and Tourism, the Village Government, the Tourism Awareness Group, and Visitors are relay actors. The finding of this study is that most stakeholders converge in support of achieving the strategic objectives, although some resist the purposes. It can be recommended to develop a pattern of collaboration between all stakeholders needed for the sustainable development of tourism potential in Ngebel Lake.